A CLIL community at work : an ethnographic case study of a Finnish early childhood education centre - Holmila, Zoe (2019)
The thesis describes an ethnographic case study research carried out at a public early childhood education centre (ECEC) in Central Finland. The aim of the study was to gain a deep understanding of the current implementation of content and language integrated learning (CLIL) provision, with a view to how this may be developed in the future. The views of multiple stakeholders were sought and this study aims to reflect the views, beliefs and practices of staff, parents and children at the ECEC. Multiple data collection tools were used to provide a rich data set, which would allow for triangulation. Semi-structured group interviews, observations, and questionnaires were among the tools selected for this study. Semi-structured interviews were conducted in four groups of three to four staff members in each. The interviews with staff were recorded and then analyzed using qualitative content analysis to answer the research questions. The research identified the key challenges which the various stakeholders face in terms of CLIL practices at the ECEC. The research also identified positive beliefs, feelings and outcomes surrounding CLIL. Finally, the study considers ideas for the continued development of CLIL at the ECEC.